Global Financial Crisis of 2008, Asymmetric Effects of Exchange Rate Changes, and Stability of the Demand for Money in Japan - Bahmani-Oskooee, Mohsen; Baek, Jungho (Journal of Reviews on Global Economics, 2016)
We wonder if Global Financial Crisis of 2008 affected stability of the demand for money in Japan. In testing this hypothesis we deviate from previous studies which either excluded the exchange rate from money demand function in Japan or have not been able to find any significant relation between the exchange rate and the demand for money. While we address stability of the demand for money, we show that failure to find a cointegrating relation or significant effects could be due to assuming a linear model in which exchange rate changes have symmetric effects. Once we consider a nonlinear ARDL approach of Shin et al.'s (2014), we show that not only variables in the money demand are cointegrated but exchange rate changes have asymmetric effects. In the long run, while appreciation of yen has significantly positive effect on the demand for money in Japan, depreciation does not. We also find a stable money demand which was not affected by 2008 financial crisis.